Study of the effects of flavonoidcontaining composition Proteflazid on modeled papillomavirus infection in vitro - Spivak, M.Ya.; Rybalko, S.L.; Starosyla, D.B.; Zavelevich, M.P.; Oleksiienko, I.P.; Diadiun, S.T.; Rudenko, A.V.; Atamaniuk, V.P. (Reports of the National Academy of Sciences of Ukraine, 2018)
A model permissive for the reproduction of human papillomaviruses (HPV) is developed by transfecting MT-4 and BHK cells with DNA isolated from cervical epithelium of the patients with papillomavirus infection. The steadily transfected cells maintain the high level of viral load. In cell sections, the intracellular viral particles and nucleocapsids are revealed under electron microscopic studies. The domestic flavonoid-containing composition Proteflazid inhibits the replication of viral DNA and normalizes the mitotic indices in transfected cells. HPV inhibition is in line with increased expression of cell proteins, which are products of tumor suppressor genes.